2008
DOI: 10.1021/jp804400s
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Second Hyperpolarizabilities of Singlet Diradical Square Planar Nickel Complexes Involving o-Semiquinonato Type Ligands

Abstract: Hybrid density functional theory method is applied for investigating the diradical character dependence of the second hyperpolarizability (gamma) of square planar nickel complexes involving several types of bidentate ligands [o-C6H4XY, where X = Y = O, NH, S, Se, and PH as well as (X, Y) = (NH, NH2) and (S, NH2)]. It is found that, as a function of the donor atoms, the diradical character of these complexes varies from 0.0 to 0.884 and is associated with substantial variations of gamma ranging from 14 x 10(3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 57 publications
4
37
0
Order By: Relevance
“…10 for the case of the isolated Ni compound. It is observed that the intramolecular charge transfer (p-> p*) over the ligands (S,C), describes the first and strong UV-Vis transition, similar to what was found for other studied metal complexes [12,50,55]. The metal d orbital (d xz ) contributes to LUMO to a minor extent only [55].…”
Section: Spectral Characteristicssupporting
confidence: 74%
See 4 more Smart Citations
“…10 for the case of the isolated Ni compound. It is observed that the intramolecular charge transfer (p-> p*) over the ligands (S,C), describes the first and strong UV-Vis transition, similar to what was found for other studied metal complexes [12,50,55]. The metal d orbital (d xz ) contributes to LUMO to a minor extent only [55].…”
Section: Spectral Characteristicssupporting
confidence: 74%
“…Two functionals were used in the calculations: (i) the PW91LYP using the aug-cc-pVTZ basis set for Ni,C,S,H,O atoms [37], and (ii) the BHandHLYP [38], employing the 6-31G* basis set for C,S,H,O [39], while for Ni a quasirelativistic effective core pseudopotential was employed (ECP28MWB (SDD) [40]). The second functional has been proven to provide reliable values of the second hyperpolarizability for a series of Ni compounds [12].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations